Synthesis of functionalized coumarins and quinolinones by NHC-catalyzed annulation of modified enals with heterocyclic C-H acids - Yetra, Santhivardhana Reddy; Roy, Tony; Bhunia, Anup; Porwal, Digvijay; Biju, Akkattu T. (Journal of Organic Chemistry, 2014)
N-Heterocyclic carbene (NHC) catalyzed lactonization and lactamization of 2-bromoenals with heterocyclic C–H acids proceeding via the α,β-unsaturated acyl azolium intermediates is reported. The reaction furnished coumarin- or quinolinone-fused lactone/lactam derivatives. In addition, results of the enantioselective version of this reaction using chiral NHC are presented.